Reflexões Sobre o Fazer Pedagógico do Professor de Química no Ensino Médio na Perspectiva do Ensino Ativo. - Façanha, Alessandro Augusto de Barros (2010)
This study investigates the pedagogical practice of Chemistry teachers of high school and the relationship of this action with the formation process and the influences present in the pedagogical actions of each teacher in his professional practice so this study seeks to characterize these professionals and relate such practices to the principles recommended by the high school curriculum guidelines which predict a behaviour based on the active – constructivist teaching. Thus understanding the degree of teachers’ knowledge about methodologies and the influence of initial and continuing formation in this process, moreover seeks to reveal what knowledge is involved in the teaching practices and from where it comes. It was used a case study through participant observation as a strategy of research and interviews as a means of data collection. The theoretical framework revisited the work of teachers and their practices from the perspectives of teachers’ knowledge and the main assumptions of active teaching based in authors like Tardif and Pimenta, besides theorists such as Piaget and Vygotsky in the review of the concepts of Piaget’s theory and Vygotskian socio-interactionism. In the analysis of the results it is possible to perceive the influences of experience as an important mark in the science/chemistry teaching besides the gaps in the early training of these teachers concerning to the active teaching aspects which demonstrate a misalignment between the proposals for the teaching of nature sciences, provided by LDB/96 and the training of these teachers. Finally the findings must be observed according to the process of scientific literacy indicating possibilities to make the teaching of Chemistry a factor in the formation of the student in his social context from a teaching based on the active construction of knowledge